2017
DOI: 10.1097/jan.0000000000000197
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors Affecting Smartphone Addiction in University Students

Abstract: Smartphone addiction is a recent concern that has resulted from the dramatic increase in worldwide smartphone use. The purpose of this cross-sectional study was to evaluate psychosocial factors affecting smartphone addiction in university students. The study was performed among students at the Ondokuz Mayis University Samsun School of Health (Samsun, Turkey) on October-December 2015. Four hundred ninety-four students possessing smartphones and agreeing to participate were included. A sociodemographic data form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
2
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 2 publications
4
52
2
8
Order By: Relevance
“…Studies have shown bidirectional influence of smartphone and psychiatric conditions. Some suggest smartphone addiction can cause insomnia, restlessness, stress, depression and impulsive behavior, [22,23] whereas some studies show these disorders could facilitate smartphone addiction [24]. These conflicting evidences warrant further studies.…”
Section: Discussionmentioning
confidence: 96%
“…Studies have shown bidirectional influence of smartphone and psychiatric conditions. Some suggest smartphone addiction can cause insomnia, restlessness, stress, depression and impulsive behavior, [22,23] whereas some studies show these disorders could facilitate smartphone addiction [24]. These conflicting evidences warrant further studies.…”
Section: Discussionmentioning
confidence: 96%
“…However, a negative association between smartphone addiction and depression was reported by another study [26]. Furthermore, another study stated that familial social support was a significant predictor of smartphone addiction, as this addiction increased as individuals’ familial support decreased [27]. There is no doubt that social relationships have been severely affected with the introduction of various social networks, and this phenomenon is commonly reported by the older generation who lived in the era before the introduction of smart phone technology.…”
Section: Discussionmentioning
confidence: 99%
“…There is no doubt that social relationships have been severely affected with the introduction of various social networks, and this phenomenon is commonly reported by the older generation who lived in the era before the introduction of smart phone technology. Unfortunately, there are gaps in literature on the probable association between smartphone addiction and social support [27]. Over usage of smartphones causes problems with attention and focusing, as these people are more likely to show more functional impairments that interfere with school, work and family life [28].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, users who most frequently use social networks on their smartphone tend to develop addictive habits faster (Jeong, Kim, Yum, & Hwang, 2016). Numerous cross-sectional investigations have identified that users with lower levels of social support show also higher levels of smartphone addiction (Aker, Sahin, Sezgin, & O uz, 2017;Billieux, Philippot et al, 2015;Ihm, 2018;Kim, 2017Kim, , 2018Kwon, So, Han, & Oh, 2016;Lu et al, 2011). Longitudinal studies in this field are less frequent.…”
Section: Smartphone Addiction As a Consequence Of Low Social Supportmentioning
confidence: 99%